T-lymphocytes suppression by CD14+ monocytes with high expression of ULK2 in patients with multiple myeloma - Fengping Peng; Zhaoyun Liu; Fengjuan Jiang; Nianbin Li; Hao Wang; Nanhao Meng; Hui Liu; Kai Ding; Rong Fu (Journal of Translational Medicine)
Abstract Background Multiple myeloma (MM), a plasma cell malignancy, remains incurable and is highly prone to relapse. Immunosuppressive cells in the bone marrow environment inhibit endogenous T-lymphocytes activity and reduce the efficacy immunotherapies. Abnormal bone marrow monocytes in MM have been associated with inferior outcomes. This study explored the mechanism of T-lymphocytes suppression by bone marrow CD14+ monocytes in MM. Methods Single-cell RNA sequence data (GSE124310) derived from MM samples were analyzed. CD14+ monocytes from the bone marrow of patients with newly-diagnosed MM were detected, and RNA sequencing was performed. Interactions between CD14+ monocytes and T-lymphocytes, as along with the corresponding downstream signaling mechanism, were assessed through in vitro and in vivo experiments. Results The alterations in MHC II signaling related to outgoing interaction were decreased in CD14 + monocytes from patients with MM. Abnormal numbers, defective antigen presentation, and downregulated surface co-stimulatory molecules in bone marrow CD14+ monocytes were also observed. RNA sequencing identified upregulated expression of Unc-51 like autophagy activating kinase 2 (ULK2) in these monocytes, a protein involved in the antigen processing and presentation pathway. CD14+ monocytes from patients with NDMM suppressed T-lymphocyte activity, and treatment of CD14+ monocytes with a ULK1/ULK2 inhibitor alleviated this suppression. MM xenograft model showed that CD14+ monocytes high-expressing ULK2 suppressed T-lymphocytes and promoted tumor growth. Conclusion We demonstrated that CD14+ monocytes from MM can disrupt the delivery of antigenic peptides through the antigen processing and presentation pathway. This disruption affects T-lymphocytes activity and attenuates their ability to kill malignant cells and secrete cytokines. These findings lay the foundation for understanding the immuno-suppressive environment in MM, improving the efficacy of immunotherapy based on T-lymphocytes, and developing new therapeutic targets.